(E)‐3‐(Benzo[b]thiophen‐2‐yl)‐2‐(3, 4, 5‐trimethoxyphenyl)acrylonitrile and (Z)‐3‐(benzo[b]thiophen‐2‐yl)‐2‐(3, 4‐dimethoxyphenyl)acrylonitrile. Corrigendum. (11th April 2013) - Sonar, Vijayakumar N.; Parkin, Sean; Crooks, Peter A.
<x xml:space="preserve">Abstract</x> The chemical names of the title compounds in the paper by Sonar et al. [Acta Cryst. (2007), C63, o743o745] are corrected.